2020
DOI: 10.3390/molecules25143184
|View full text |Cite
|
Sign up to set email alerts
|

Syntheses and Reactivity of New Zwitterionic Imidazolium Trihydridoborate and Triphenylborate Species

Abstract: In this study, four new N-(alkyl/aryl)imidazolium-borates were prepared, and their deprotonation reactions were investigated. Addition of BH3•THF to N-benzylimidazoles and N-mesitylimidazoles leads to imidazolium-trihydridoborate adducts. Ammonium tetraphenylborate reacts with benzyl- or mesityl-imidazoles with the loss of one of the phenyl groups yielding the corresponding imidazolium-triphenylborates. Their authenticity was confirmed by CHN analysis, 1H-NMR, 13C-NMR, 11B-NMR, FT-IR spectroscopy, and electros… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...

Citation Types

0
1
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 110 publications
(182 reference statements)
0
1
0
Order By: Relevance
“…The NHCs which constitute the most developed family of neutral carbon ligands have been approached from two main directions by the different contributors, namely, from a synthetic point of view with the preparation of new carbenic structures, and for their applications either in catalysis or in biology. In the first direction, while Kunz et al described the fascinating coordination chemistry of a strongly donor macrocyclic C,N,C -pincer ligand exhibiting pentamethylene tethered NHC donor ends [ 12 ], Dias et al were interested in the design of Hg(II) complexes bearing anionic maloNHC ligands [ 13 ], and Santini et al in the chemistry of zwitterionic imidazolium borate species [ 14 ]. Regarding catalytic applications, Grela et al reported the preparation of a family of nitro-activated Ru(II)-based olefin metathesis catalysts while evaluating the influence of the NHC ligand [ 15 ].…”
mentioning
confidence: 99%
“…The NHCs which constitute the most developed family of neutral carbon ligands have been approached from two main directions by the different contributors, namely, from a synthetic point of view with the preparation of new carbenic structures, and for their applications either in catalysis or in biology. In the first direction, while Kunz et al described the fascinating coordination chemistry of a strongly donor macrocyclic C,N,C -pincer ligand exhibiting pentamethylene tethered NHC donor ends [ 12 ], Dias et al were interested in the design of Hg(II) complexes bearing anionic maloNHC ligands [ 13 ], and Santini et al in the chemistry of zwitterionic imidazolium borate species [ 14 ]. Regarding catalytic applications, Grela et al reported the preparation of a family of nitro-activated Ru(II)-based olefin metathesis catalysts while evaluating the influence of the NHC ligand [ 15 ].…”
mentioning
confidence: 99%